In my reference book, Lawrence Perko's Differential Equations, the following nonlinear system of differential equations

$$\begin{bmatrix} \dot{x_1}\\\dot{x_2} \end{bmatrix}=\begin{bmatrix} -x_1\\x_2+x_1^2 \end{bmatrix}$$

with initial condition $c = (c_1, c_2)$ has the following solution

$$\begin{bmatrix} c_1e^{-t}\\ c_2e^t+\frac{c_1^2}{3}(e^t-e^{-2t}) \end{bmatrix}$$

I understand that $x_1 = c_1 e^{-t}$ can be obtained by separating variables. After that, if we substitute that in second equation, it becomes:

$$\begin{align} \dot{x_2}&=x_2+(c_1e^{-t})^2 \\ \dot{x_2}-x_2&=c_1^2e^{-2t}\\ e^{-t}\dot{x_2}-e^{-t}x_2 &=c_1^2e^{-3t}\\ \frac{\mathrm{d}(e^{-t}x_2) }{\mathrm{d} t}&=c_1^2e^{-3t}\\ \therefore e^{-t}x_2&=\int c_1^2e^{-3t}dt+c_2 \end{align}$$

But from this I don't see a way to obtain the given solution. Help would be appreciated


By evaluating the integral $$ e^{-t}x_2(t)=c_1^2\int e^{-3t}\mathrm dt+c_2=\frac{-c_1^2}{3}e^{-3t}+c_2+C $$ where $C$ is an integration constant. Moving the exponential over to solve for $x_2$, we have $$ x_2(t)=\frac{-c_1^2}{3}e^{-2t}+e^{t}c_2+Ce^{t} $$ Plugging in $x_2(0)=c_2$ yields the solution.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.